Predictive modelling of biogas generation from palm oil mill effuent for the wastewayer-energy nexus - Nur Hazirah Che Ithnin, 1993-, author 641548 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Sains (Pengurusan Tenaga))